2011
DOI: 10.1007/s13592-011-0108-7
|View full text |Cite
|
Sign up to set email alerts
|

Plant essential oils and formamidines as insecticides/acaricides: what are the molecular targets?

Abstract: The parasitic mite Varroa destructor is the main cause of the severe reduction in beekeeping during the last few decades. Therefore, efforts have been made to develop chemical treatments against the parasite. In the past, synthetic products were preferentially used to combat Varroa mites. Nowadays, mainly plant essential oils and organic acids are applied because they are safer and impose less unfavorable effects on the environment. Essential oils contain mixtures of mostly volatile and odorous terpenoid const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 91 publications
2
69
1
2
Order By: Relevance
“…While the diverse physiological functions of octopamine have been realized for some time, we are only starting to understand the physiological relevance of tyramine; this is because, until recently, tyramine was thought to only be a synthetic precursor to octopamine (Guerrero and Dowd, 2010;Roeder et al, 2003;Roeder, 2005;Verlinden et al, 2010;Farooqui, 2012). Octopamine receptors are believed to be the target of formamidine insecticides/acaricides, which include chlordimeform and amitraz (Blenau et al, 2012;Hashemzadeh et al, 1985). Hyperactivity and tick detachment are symptoms of exposure to sublethal concentrations of formamidine acaricides against the southern cattle tick (Stone et al, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…While the diverse physiological functions of octopamine have been realized for some time, we are only starting to understand the physiological relevance of tyramine; this is because, until recently, tyramine was thought to only be a synthetic precursor to octopamine (Guerrero and Dowd, 2010;Roeder et al, 2003;Roeder, 2005;Verlinden et al, 2010;Farooqui, 2012). Octopamine receptors are believed to be the target of formamidine insecticides/acaricides, which include chlordimeform and amitraz (Blenau et al, 2012;Hashemzadeh et al, 1985). Hyperactivity and tick detachment are symptoms of exposure to sublethal concentrations of formamidine acaricides against the southern cattle tick (Stone et al, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…AChE besides cholinergic transmission is related to several non-cholinergic actions such as responses to stress situations. Stress can increase due to free radicals which impair enzyme function (Gutierres et al, 2012(Gutierres et al, , 2014 and lead to disorders in locomotion (Blenau et al, 2012) and fish erratic swimming (Salbego et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The inhibitory effect of EOL was expected since the main compound present in this chemotype is linalool (Vale et al, 1999(Vale et al, , 2002, which has been shown to inhibit AChE in insects (Blenau et al, 2012) and in the electric eel, Electrophorus electricus (López et al, 2015). EUG has also been shown to inhibit AChE in the electric eel (López et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Acetylcholinesterase (AChE) is an enzyme present in cholinergic synapses and at motor end plates, which is responsible for degrading acetylcholine (ACh) at the synaptic level, and is extremely important for many physiological functions in fish (Blenau et al, 2012;Salbego et al, 2014). The effect of anesthetics on AChE activity is poorly documented (Mazzanti et al, 1986;Lintern et al, 2000).…”
Section: Introductionmentioning
confidence: 99%